(untitled) - Pomeranchuk, I. Ya (New Jersey, 2003)
This conference was dedicated to the memory of the great scientist and teacher I Ya Pomeranchuk on the occasion of his 90th birthday. It was multidisciplinary and covered those fields of physics where Pomeranchuk made outstanding contributions — including high energy physics, quantum field theory, theory of liquid helium, condensed matter physics, physics of electromagnetic processes in matter, and astrophysics. Most of the plenary talks and reports were given by Pomeranchuk’s former students and coworkers.
Keywords: Physics; History